2022
DOI: 10.1177/17531934221088498
|View full text |Cite
|
Sign up to set email alerts
|

The effects of partial wrist denervation in wrist osteoarthritis: patient-reported outcomes and objective function

Abstract: This prospective longitudinal study aimed to analyse the effect of partial wrist denervation on patient-reported outcomes, quality of life and objective function in symptomatic wrist osteoarthritis during the first year after surgery. Sixty consecutive patients underwent an anterior and posterior interosseous neurectomy during 2018–2020. Disabilities of the Arm, Shoulder and Hand, Patient-Rated Wrist Evaluation, EuroQol-5D-3L, pain at rest and on load, and objective function were assessed preoperatively and 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In an uncontrolled trial, analytical (rather than descriptive) statistics would be applied to test a pre-defined hypothesis. The following example of an uncontrolled experimental study (Sw€ ard et al, 2022) examined the effects of partial wrist denervation in wrist osteoarthritis through patient-reported outcomes and objective function. The authors themselves highlight key limitations of this study design, namely the lack of control group or blinding leading to high risk of bias and confounding variables (mitigated somewhat by use of statistical methods).…”
Section: Non-randomized Experimental Studiesmentioning
confidence: 99%
“…In an uncontrolled trial, analytical (rather than descriptive) statistics would be applied to test a pre-defined hypothesis. The following example of an uncontrolled experimental study (Sw€ ard et al, 2022) examined the effects of partial wrist denervation in wrist osteoarthritis through patient-reported outcomes and objective function. The authors themselves highlight key limitations of this study design, namely the lack of control group or blinding leading to high risk of bias and confounding variables (mitigated somewhat by use of statistical methods).…”
Section: Non-randomized Experimental Studiesmentioning
confidence: 99%
“…Loss to follow-up, a lack of a firm endpoint, and temporary relief of symptoms are all issues with accurately reporting the outcome in these patients. Authors from Stockholm (Sweden) have reported their prospective longitudinal series of patients undergoing partial wrist denervation of the anterior interosseous nerve (AIN) and posterior interosseous nerve (PIN) over a two-year period to 2020 5. Via a dorsal approach, a PIN neurectomy was performed before an incision through the intraosseous membrane allowed a neurectomy of the terminal branches of the AIN.Operations were performed by experienced but not expert surgeons under either regional orlocal anaesthesia.…”
mentioning
confidence: 99%